THE UTILIZATION OF TRADITIONAL MEDICINAL PLANTS BY THE COMMUNITY AROUND THE FOREST WILDLIFE SANCTUARY A COMPLEX OF PELALAWAN REGENCY RIAU PROVINCE - Hardi Yuda; Defri Yoza; Viny Volcherina (Jurnal Ilmu Ilmu Kehutanan, 2019)
Wildlife Reserve is a nature reserve forest that is designed as a place for wildlife that has distinctive value and beneficial for science and culture, also a source of national wealth and pride. This research was conducted to find out the use of traditional medicinal plants in Kerumutan Wildlife Reserve and approach the surrounding community. The type of data used in this study are primary data and secondary data. The population in this study were all communities around the Wildlife Reserve area. This research used purposive sampling, with research procedures namely interviews and observations. Observations were made using 1 observation track, located in natural forest. The track has long 1.5 km, which has 30 observation plots sized 5 m x 5 m. The distance between the plots was 30 m from the first plot to the next plot. The results showed there were 27 species with 19 families of medicinal plants that could be used and processed into medicines in the Kerumutan Wildlife Reserve forest area. Different uses and processing of plant species can produce medicines that can treat diseases suffered by the community. Medicinal plants were most widely used by the community as a febrifuge and abdominal pain.